CHARLES DICKENS AS A FOUNDER OF CHRISTMAS GENRE IN BRITISH LITERATURE - Mo’ydinova Umida; Eldorbek Erkinovich Hamitov (Ta’lim innovatsiyasi va integratsiyasi, 2024)
This article examines the pivotal role of Charles Dickens in establishing the Christmas genre within British literature. Through an analysis of his iconic works such as "A Christmas Carol," "The Chimes," and "The Cricket on the Hearth," the paper explores how Dickens transformed Christmas into a symbol of generosity, redemption, and familial warmth. By blending elements of social commentary with heartwarming narratives, Dickens popularized traditions such as feasting, gift-giving, and goodwill, shaping the modern celebration of Christmas. Through his vivid characters and timeless themes, Dickens's influence on the festive season resonates to this day, making him a foundational figure in the Christmas literary canon.